Boron: More Than an Essential Element for Land Plants? - Pereira, Greice Leal; Siqueira, João Antonio; Batista-Silva, Willian; Cardoso, Flávio Barcellos; Nunes-Nesi, Adriano; Araújo, Wagner L. (Frontiers in Plant Science, 2021)
Although boron (B) is an element that has long been assumed to be an essential plant micronutrient, this assumption has been recently questioned. Cumulative evidence has demonstrated that the players associated with B uptake and translocation by plant roots include a sophisticated set of proteins used to cope with B levels in the soil solution. Here, we summarise compelling evidence supporting the essential role of B in mediating plant developmental programs. Overall, most plant species studied to date have exhibited specific B transporters with tight genetic coordination in response to B levels in the soil. These transporters can uptake B from the soil, which is a highly uncommon occurrence for toxic elements. Moreover, the current tools available to determine B levels cannot precisely determine B translocation dynamics. We posit that B plays a key role in plant metabolic activities. Its importance in the regulation of development of the root and shoot meristem is associated with plant developmental phase transitions, which are crucial processes in the completion of their life cycle. We provide further evidence that plants need to acquire sufficient amounts of B while protecting themselves from its toxic effects. Thus, the development of in vitro and in vivo approaches is required to accurately determine B levels, and subsequently, to define unambiguously the function of B in terrestrial plants.